TRENDS IN IMPLEMENTATION OF TECHNOLOGY USE IN MATHEMATICS EDUCATION ON SCOPUS DATABASE: BIBLIOMETRIC ANALYSIS - Bin Zabidi, Muhammad Aqil Naim; Bakti, Anugrah Arya; Sultan, Jumriani; Ayuni, Rizki Tika; Arriza, Lovieanta (UIR PRESS, 2024)
This study aims to analyze the trend of technology implementation in mathematics education in the Scopus Database using bibliometric analysis. Using predetermined keywords, researchers analyzed 251 documents using RStudio and Vosviewer. From the analysis conducted, it can be concluded that this study shows an interesting growth pattern in research on the use of technology in mathematics education over the period 1977 to 2024. This pattern changed significantly in the last 15 years, from 2009 to 2024, which is equivalent to four times the previous figure, or 66.13% of the total. The University of Pretoria dominated with the highest number of publications, at 14 articles. The source